1994
DOI: 10.1111/j.1365-2052.1994.tb00446.x
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced differences in the frequency of TaqI βA‐inhibin alleles between sheep breeds with different reproductive performance

Abstract: A total of 419 individuals of four breeds with differing fecundity (Rhoenschaf, Merinolandschaf, East Friesian Milksheep, Romanov) and several wild sheep of the Ovis musimon, 0. orientalis, 0. vignei and 0. ammon groups were screened for genetic variation at the PA-inhibin (INHBA) locus with up to 11 enzymes. The four breeds differed significantly (P < 0.001) in TaqZ allele frequencies. The frequency of the TaqZ A allele coincided with the average litter size in each breed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…2007). Leyhe et al . (1994) showed that INHA gene had TaqI restriction fragment length polymorphism (RFLP), and TaqI A allele associated with average litter size in sheep breeds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2007). Leyhe et al . (1994) showed that INHA gene had TaqI restriction fragment length polymorphism (RFLP), and TaqI A allele associated with average litter size in sheep breeds.…”
Section: Discussionmentioning
confidence: 99%
“…(2009) reported that variants in the promoter region of the INHA gene were associated with premature ovarian failure. The important roles of the INHA and INHβA genes in reproduction make it a strong candidate gene for multi‐births in mammals such as sheep (Leyhe et al . 1994; Wu et al .…”
Section: Introductionmentioning
confidence: 99%
“…An animal model analysis revealed that the substitution effect of INHβA reached 0.04 lambs in Merinolandschaf ewes and 0.09 lambs in East Friesian Milksheep ewes (Hiendleder et al, 1996a). One TaqI restriction fragment length polymorphism was detected in sheep breeds, which was significantly associated with litter size (Leyhe et al, 1994;Hiendleder et al, 1996b). Chu et al (2007) identified 21 new SNPs of INHβA that significantly influenced litter size in Small Tail Han sheep.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that INHα gene had the significant additive effect on the sheep prolificacy, INHA, INHBA, and INHBB had obviously gene effect on litter size [Jaeger, et al, 1994;Hiendleder, et al, 1996;Hiendleder, et al, 2002]. Another study showed that INHα gene had TaqI restriction fragment length polymorphism (RFLP), and TaqI A allele associated to the average litter size on sheep breed [Leyhe, et al, 1994;Sise, et al,1991]. In this study, we found a mutation (C865T) for the first time existed in the exon of the gene, which made an obviously difference in the gene frequency and the genotype frequency between the year-round estrous goat breed and the seasonal estrous goat breeds.…”
Section: Discussionmentioning
confidence: 99%